The principles formation of sustainable development of oil and gas companies - A. V. Kolesnikova; А. В. Колесникова (Vestnik Universiteta, 2023)
The basis of the successful sustainable development of the country is based on the design and development of the principles of sustainable development by the largest companies. The issue of searching for options for changing and improving the mechanism for sustainable development of oil and gas companies and the development of their methodological and legal support is acute on the agenda of the management of the companies themselves, as well as in the framework of research at the state level. In connection with the growing geopolitical threats, the increasing pressure of oil-producing countries on pricing and production levels, participation in the development of the Arctic shelf, as well as the internal problems of the Russian Federation and the companies themselves, which are strategically important in the country’s economy, the necessity and need for the development and improvement of the sustainable development mechanism are relevant and justified. Purpose of the study – to determine the place occupied by oil and gas companies among other industries of the Russian Federation in the field of sustainable development and the level of disclosure of their financial and non-financial statements. Research objectives; to analyze the results of the reports of the main rating agencies of the Russian Federation; to identify bottlenecks – strengths and weaknesses of oil and gas companies. Consider the possibility of improving the sustainable development mechanism. Research results are as follows. Based on the analysis of the existing theoretical framework in the field of sustainable development , as well as the results of the main national ratings, bottlenecks were identified in the publication of oil and gas companies reports. A variant of improving the mechanism of sustainable development of the functioning of oil and gas companies is proposed. Основа успешного устойчивого развития страны опирается на разработку и развитие принципов устойчивого развития крупнейшими компаниями. Вопрос поиска вариантов изменения и ...